Conference On Physician's Assistants [at Duke University] - Correspondence: Howard to Anlyan - Howard, D. Robert (1968)
In his October 3, 1968 letter to Dr. William Anlyan, Dean of the Medical School, Dr. D. Robert Howard indicates that the AMA Council on Medical Education will not be sponsoring the conference scheduled for October 28-29 at Duke University. However because of the interest expressed in PAs, the Department of Community Health Sciences had decided to sponsor the conference. Cost would be covered by charging a $10 registration fee. A copy of the tentative agenda and a mockup program are attached to the letter. The Statler Hilton Inn is designated as the site of the Conference.